Impact of Work Environment, Job Stress, and Compensation on Employee Performance in the Palm Oil Plantation Industry - Rita Deseria; Putria Lestari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study examines the impact of work environment, job stress, and compensation on employee performance within the palm oil plantation industry. Using quantitative analysis, we assessed the influence of these variables through a t-test, where findings indicated that each factor significantly affects employee performance. Results showed a positive and significant relationship between work environment and performance, highlighting that a supportive environment enhances productivity, while disruptive conditions, such as noise from adjacent guest areas, reduce focus and output. Job stress was also found to have a positive impact on performance when kept within employees’ capacity, as manageable levels of stress can motivate employees and drive productivity. However, excessive stress has a detrimental effect on performance. Compensation emerged as a critical factor, aligning with Maslow's Hierarchy of Needs, where adequate financial rewards foster employee motivation and job satisfaction, subsequently boosting performance. The company's compensation structure revealed discrepancies, with core employees receiving wages aligned with the provincial minimum wage, while plasma employees were paid hourly, impacting overall motivation and productivity. This study contributes to human resource management practices by underscoring the importance of a balanced work environment, manageable stress levels, and fair compensation in optimizing employee performance. Future research could explore mediating factors such as job satisfaction and employee engagement, as well as comparative analysis across different industries to provide broader insights into these dynamics.